Study of the influence of the deposition rate of dust and fine aerosol particles for monitoring and forecasting the state of the surface layer of the atmosphere in industrial regions - Ravshanov, Normakhmad; Tashtemirova, Nadira; Ubaydullaev, Malik (International Journal of Innovative Research and Scientific Studies, 2025)
For the stable development of society, one of the factors is air quality control, since today reducing the negative impact of pollutants on human health and the ecosystem is especially relevant and in demand. Based on the above, the article examines an important factor: the movement of gravitational deposition of dust and fine aerosol particles on the Earth’s surface, which depends on the physical properties of the dispersion phase, temperature, dynamic and kinematic viscosity of the atmospheric air mass, and the horizontal and vertical components of wind speed. Atmospheric stratification affects the deposition of harmful substances in the atmosphere. A mathematical model is presented that takes into account the rate of particle sedimentation, where formulas are provided for calculating it depending on the physical and mechanical properties and characteristics of the medium. For the settling rate of spherical aerosol particles, the Stokes equation is used, which considers all the forces influencing the settling rate. To calculate the dynamic and kinematic viscosity of air, which significantly influences the deposition rate of dust and fine aerosol particles, a regression model is provided that takes into account the temperature and pressure of the atmospheric air mass, and the results of numerical calculations are presented in the form of graphs and histograms.